Jambangan Resident's Participation in Processing Organic Waste with Composter at Household Scale - Winarsih; Suyadi; Efani, Anthon; Yanuwiadi, Bagyo (Jurnal Pembangunan dan Alam Lestari, 2024)
Organic waste easily emits horrible smells if not quickly processed. One way to process organic waste is by using an aerobic composter on a household scale. Organic waste processing has been socialized through the Department of Hygiene and Parks of Surabaya since 2002. This study aims to measure Jambangan village residents' participation rate in processing organic waste with composters. The method of this study is a survey of the Jambangan village residents that have installed the composters and have the space to place the composters. The data will then be analyzed with descriptive statistics. The data shows that Jambangan village residents' participation rate in processing organic waste with aerobic composters is very low. This is caused by a lack of knowledge and awareness among the public, combined with limited space availability. These factors contribute to the low participation rate of the community in organic waste processing. Keywords: composter,  jambangan village, participation, organic waste